Potency of Turmeric (Curcuma longa L.) and Temulawak (Curcuma xanthorrhiza Roxb.) in Handling Coronavirus Disease 2019 (COVID-19) - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2022)
One of the efforts to prevent COVID-19 that can be done is to increase individual immunity. The effort that can be made is to use herbal ingredients as health drinks. Curcuma longa L., or turmeric, has long been known as one of the ingredients used to treat several complaints. Turmeric has a chemical content of carbohydrates (69.4%), curcuminoids, and essential oils (5.8%). Turmeric and curcumin are non-mutagenic, and no reproductive toxicity has been observed. Curcuma xanthorrhiza Roxb, also known as temulawak, contains curcuminoids (1-2%) and essential oils with xanthorrhizol components (31.9%), ß-curcumene (17.1%), arcurcumene (13.2%), camphor (5.4%), γ-curcumene (2.6%), (Z)-γ-bisabolene (2.6%), and (E)-ß-farnesene (1.2%). Empirically, temulawak has been used for generations in Indonesia to treat various digestive disorders, skin complaints, liver and bile disorders.